Earmarking in the multilateral development system: Many shades of grey - Silke Weinlich; Max-Otto Baumann; Erik Lundsgaarde; Peter Wolff (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Earmarking financial contributions for specific geographic, thematic or other priorities has emerged as an important modality for funding multilateral development organisations. Earmarking has had positive consequences, such as the mobilisation of resources for multilateral organisations and new partnership modalities, including with non-state actors. Yet, there has been a rising concern about challenges relating to the effectiveness, efficiency and legitimacy of multilateral development cooperation. Understanding and addressing these negative aspects has gained a new urgency. The 2030 Agenda for Sustainable Development and the crisis of multilateralism make it imperative to tackle the downsides of earmarked funding and bring out its positive forces. This study was commissioned by the German Ministry for Economic Cooperation and Development. Germany is a latecomer to earmarking - the government has begun only in recent years to make use of earmarked funds at a larger scale. The study analyses the most important instruments of earmarked funding, studies practices of selected donors that supply large shares of earmarked funding, and analyses practices and consequences of earmarked funding with regard to the UN Development System and multilateral development banks. The study concludes with recommendations to the German government on how to improve its earmarking practices.
Keywords: 330; Entwicklungsfinanzierung; Entwicklungsorganisation; Deutschland; Großbritannien; Schweden; EU-Staaten